2008
DOI: 10.1002/nau.20600
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract dysfunction in familial amyloidotic polyneuropathy, Portuguese Type

Abstract: In addition to reduced sensation, underactive detrusor, opening of the vesical neck and external sphincter deficit, we found data suggesting failure of relaxation of the internal and external sphincter. The overdistention associated with an open vesical neck and external sphincter deficit justifies incontinence in those patients. The retention is due to inadequate contraction of the detrusor, probably associated with non-relaxing of the internal and external sphincter. These dysfunctions derive from deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Andrade et al assessed lower urinary dysfunction in 54 familial amyloidotic polyneuropathy patients. 69 Initial urinary symptoms, including dysuria, incontinence, and sensitivity and contractility disturbances of the detrusor, appeared during the first 3 years of the disease in 50% of their patients. Vesicosphincter dysfunction in familial amyloid polyneuropathy (FAP) occurs at an early stage of the disease even in asymptomatic patients.…”
Section: Hiv-associated Neuropathymentioning
confidence: 99%
See 2 more Smart Citations
“…Andrade et al assessed lower urinary dysfunction in 54 familial amyloidotic polyneuropathy patients. 69 Initial urinary symptoms, including dysuria, incontinence, and sensitivity and contractility disturbances of the detrusor, appeared during the first 3 years of the disease in 50% of their patients. Vesicosphincter dysfunction in familial amyloid polyneuropathy (FAP) occurs at an early stage of the disease even in asymptomatic patients.…”
Section: Hiv-associated Neuropathymentioning
confidence: 99%
“…The underlying pathogenesis of these dysfunctions is thought to be damage to small nerve endings and deposition of amyloid in the detrusor. 69 Ito et al performed uro-neurological assessment in 4 patients with amyloid neuropathy. All of the patients described symptoms of lower urinary tract dysfunction and had voiding difficulties due to detrusor weakness and impaired bladder sensation.…”
Section: Hiv-associated Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of FAP-1 on the genito-urinary system in both sexes are common and may be early and progressive-like previously described [4]. The natural history is typically a progressive deterioration in the function of the urinary bladder and urethra similar to other peripheral neuropathy disorders such as that associated with diabetes mellitus.…”
mentioning
confidence: 78%
“…The degree of FAP gene mutation and penetrance determines the type of lower urinary tract symptoms in carriers with storage problems occurring at a higher rate (56.5%) than voiding dysfunctions (52.2%). The first abnormality is thus diminished bladder sensation followed by reduced detrusor contractility (myogenic, vasculogenic, or neurogenic patterns) leading to incomplete voiding, urinary retention, and subsequent back-pressure complications on the upper urinary tract and chronic renal failure [4]. One study in progress has shown that the incidence of reduced bladder sensation and reduced detrusor contractility among female carriers of FAP-1 was 33% and 25%, respectively, with the former abnormality appearing earlier (unpublished observation).…”
mentioning
confidence: 95%